Evaluation of antidiabetic potential, cardio, pancreatic, nephroprotective effect, and herb-herb-drug interaction of Madhukiran formulations in T2 diabetic rats - Vrushabh S. Kondalkar; Pranali P. Polshettiwar; Ganesh B. Choudhari; Anil T. Pawar; Vishnu P. Choudhari (Phytomedicine Plus)
Background and aim: Madhukiran Powder (MP) and Madhukiran Liquid (ML) formulations are used as supportive health supplements by people suffering from type 2 diabetes (T2D) either alone or concomitantly. The present study was undertaken to substantiate their usefulness in T2D management further using in vivo models. Herb-herb interactions (HHI), and herb-drug interactions (HDI) along with antidiabetic, cardio, hepatic, pancreatic, and nephroprotective effects of Madhukiran Formulations (MFs) were studied on STZ-NA-induced T2D rats. Experimental procedure: Wistar rats were given a single intraperitoneal injection of STZ fifteen minutes after receiving an injection of NA, which caused diabetes. Hypoglycemic, antihyperlipidemic, antioxidant, cardio, pancreatic, reno, and hepatoprotective activities of MP, ML, MP+ML alone and combined with Metformin were evaluated. Histological alterations in the heart, liver, kidney, and pancreatic tissues, and biochemical alterations in the urine, plasma, heart, liver, and kidney homogenate, were evaluated. Metformin served as the reference standard drug for the efficacy study of MFs as well as for HDI studies. Results and conclusion: MFs alone, concomitantly, and with ME combination significantly decreased elevated plasma glucose level, urine volume, and urinating frequency. Significant improvements in the plasma lipid profile, HbA1C content, and liver glycogen content were seen following MP/ML supplementation. Concurrent administration of MFs improved nearly all T2D indices and restored all the histological alterations in the heart, liver, kidney, and pancreas tissues. There were no HHI or HDI associated with the notable antidiabetic and hyperlipidemic effects of MP and ML. It is concluded that MFs possess significant antidiabetic activity in rats.